2006
DOI: 10.1002/cc.244
|View full text |Cite
|
Sign up to set email alerts
|

Historically underserved students: What we know, what we still need to know

Abstract: Community colleges educate many traditionally underserved students, including students of color, first-generation students, and low-income students. This chapter discusses what we know about these students, how they have fared in college transitions, how educational pipeline and deficit models have helped or hindered their progress, and what community college educators should seek to understand about this diverse population of students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 4 publications
1
64
0
Order By: Relevance
“…Minority students commonly enter into college with lower achievement entrance examination scores (Green, 2006). Fischer (2007) suggested in her study on minority students and college transition, that in the academic realm, minority students (Blacks, Hispanics, and Asians) who had better preparation prior to college received better college grades.…”
Section: Academic Barriersmentioning
confidence: 99%
“…Minority students commonly enter into college with lower achievement entrance examination scores (Green, 2006). Fischer (2007) suggested in her study on minority students and college transition, that in the academic realm, minority students (Blacks, Hispanics, and Asians) who had better preparation prior to college received better college grades.…”
Section: Academic Barriersmentioning
confidence: 99%
“…Low income community college students do not share the same level of success as their higher-income peers (Green, 2006). Although community college students are more likely than students who attend 4-year colleges to be of lower socio-economic status, they still have goals of obtaining a certificate or degree.…”
Section: Statement Of the Problemmentioning
confidence: 97%
“…This study extends current research on levels of the self-reported stress community college students experience and their beliefs about meditation utilizing an online survey tool. The literature on the topic suggests that community college students are more likely than 4-year college students to experience stress, and they are also less likely to earn a certificate or degree (Green, 2006;Kena et al, 2015;Ryan, 2009). Specifically, community college students' characteristics are likely to be linked to stress, which can impede academic success (Bailey, 2009;Chickering & Reisser, 1993;Jenkins & Weiss, 2011;Joshi et al, 2009).…”
Section: Chapter V: Discussion Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to many EWS failing to incorporate other departments across campus to collectively help the student, metacognitive and noncognitive factors/skills and the multi-faceted (and interactive) interventions that can address them (e.g., multi-interactive educational pipeline models such as the multi-faceted EWS) are understudied and infrequently utilized in higher education, despite evidence suggesting that they contribute to retention and academic success Green, 2006;Hermanowicz, 2003;Honan & Rule, 2002;Keup, 2006;Kinzie et al, 2008;Pascarella & Terenzini, 2005;Rendon, 2006;Shivpuri, 2006;Ting et al, 2000). When institutions embrace this ideal and implement programs that take these factors into consideration, this can translate into improved cognitive and noncognitive skills, academic and social integration, and retention and persistence.…”
Section: Rationale For Studymentioning
confidence: 99%